2016
DOI: 10.3390/ijms17081277
|View full text |Cite
|
Sign up to set email alerts
|

New Natural Pigment Fraction Isolated from Saw Palmetto: Potential for Adjuvant Therapy of Hepatocellular Carcinoma

Abstract: For the first time, we discovered a small proportion of aqueous fraction from Saw Palmetto apart from the fatty acid-rich fraction exhibited pharmacological activity. Therefore, this study aims to explore the anti-tumor potential of red pigmented aqueous fraction of Saw Palmetto, NYG on human hepatocellular carcinoma and its possible targets. Subcutaneous xenograft and orthotopic implantation models of HCC were used to evaluate the tumor inhibitory effect of NYG. Human hepatocellular carcinoma (HCC) cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Physicians have used herbal medicines for disease prevention and treatment in traditional medical practices for many centuries [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Over the past few decades, studies have identified a number of natural compounds extracted from herbal medicine with potential for disease therapy [ 11 , 60 , 61 , 62 , 63 , 64 , 65 ]. Botanical drugs such as sinecatechins, cascara, psyllium, and senna are approved by the US Food and Drug Administration and similar organizations as prescription or over-the-counter drugs [ 66 ].…”
Section: Fak Inhibitors From Natural Sourcesmentioning
confidence: 99%
“…Physicians have used herbal medicines for disease prevention and treatment in traditional medical practices for many centuries [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Over the past few decades, studies have identified a number of natural compounds extracted from herbal medicine with potential for disease therapy [ 11 , 60 , 61 , 62 , 63 , 64 , 65 ]. Botanical drugs such as sinecatechins, cascara, psyllium, and senna are approved by the US Food and Drug Administration and similar organizations as prescription or over-the-counter drugs [ 66 ].…”
Section: Fak Inhibitors From Natural Sourcesmentioning
confidence: 99%
“…WO 2014174703 A1) had been extracted from saw palmetto and demonstrated to target hepatocellular carcinoma as an adjunct drug. 12…”
Section: Pharmacological Effects Of Spementioning
confidence: 99%
“…6 Meanwhile, Tan et al reported that a new substance named NYG (Patent No. WO 2014174703 A1) had been extracted from saw palmetto and demonstrated to target hepatocellular carcinoma as an adjunct drug 12. …”
mentioning
confidence: 99%